Indium-catalyzed intramolecular hydroamidation of alkynes: an exo-dig cyclization for the synthesis of pyranoquinolines through post-transformational reaction - Balalaie, Saeed; Rominger, Frank (Organic letters, 2017)
An efficient approach for the synthesis of pyranoquinolines through the indium-catalyzed activation of alkynes is reported. Intramolecular hydroamidation of alkynes can proceed through alkyne activation by indium(III) and then 6-exo-dig cyclization, leading to a fused pyran ring with high selectivity, high atom economy, and good to excellent yields. The cyclization was accomplished through the oxygen, not the nitrogen, of the amide functional group.
Gesehen am 05.09.2018